STRATEGI PT. RAJAWALI NUSANTARA INDONESIA DALAM PENGEMBANGAN INDUSTRI GULA NASIONAL - , Eddy Kuswaedi, Prof. Dr. Ir. Dwidjono Hadi Darwanto, MS ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Research about The strategic of PT. Rajawali Nusantara Indonesia (PT. RNI) on developing national sugar industry get the focus are (1) Knowing and measure internal and external factors and the influence factors of PT. RNI to developing the national sugar industry and so that knowing market position for now, and (2) Make certain about key success factors will necesarry in PT. RNI and alternative business startegy fomulation became key success factors to encounter rivalry on the future. The methods in this research is descritive analysis. The population in the research are the people will be competent to developing the national sugar industry with the manual likely quetionare. The responden composed the top management (President Director, Production and Developing Director, Human Resounce Director and Finacial Director), Corporation Secretary, Head of SPI, Deputy Director, Deputy Director Asisstant and the Employee. The conclusion of this research is developing strategic position of PT. RNI on developing sugar industry on domestic own master and had the competitiveness as one of strategic business units as quadrant I or in agresive growing stage, so it will developing strategy will be done is growth-oriented strategy (S-O strategy), S-O strategy is utilised or retaking optimum opportunity with maximizing strength